Diagnostic Accuracy of Preoperative Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios in Detecting Occult Papillary Thyroid Microcarcinomas in Benign Multinodular Goitres. (23rd April 2018) - Manatakis, Dimitrios K.; Tseleni-Balafouta, Sophia; Tzelves, Lazaros; Balalis, Dimitrios; Tzortzopoulou, Adelais; Korkolis, Dimitrios P.; Sakorafas, George H.; Gontikakis, Emmanouil; Plataniotis, Georgios
Abstract : Objective . To investigate the diagnostic accuracy of neutrophil-to-lymphocyte (NLR) and platelet-to-lymphocyte (PLR) ratios in detecting occult papillary thyroid microcarcinomas in benign, multinodular goitres. Methods . 397 total thyroidectomy patients were identified from the institutional thyroid surgery database between 2007 and 2016 (94 males, 303 females, mean age 53 ± 14.5 years). NLR and PLR were calculated as the absolute neutrophil and absolute platelet counts divided by the absolute lymphocyte count, respectively, based on the preoperative complete blood cell count. Results . NLR was significantly higher in carcinomas and microcarcinomas compared to benign pathology (p = 0.026 ), whereas a direct association could not be established for PLR. Both NLR and PLR scored low in all parameters of diagnostic accuracy, with overall accuracy ranging between 45 and 50%. Conclusions . As surrogate indices of the systemic inflammatory response, NLR and PLR are inexpensive and universally available from routine blood tests. Although we found higher NLR values in cases of malignancy, NLR and PLR cannot effectively predict the presence of occult papillary microcarcinomas in otherwise benign, multinodular goitres.